Amino acid composition, protein content, and nitrogen-to-protein conversion factors of 21 seaweed species from Norwegian waters - Biancarosa, I.; Espe, M.; Bruckner, C. G.; Heesch, S.; Liland, N.; Waagbø, R.; Torstensen, B.; Lock, E. J. (Journal of applied phycology, 2017)
The Norwegian seaweed industry is expanding and there is a need for accurate estimates of protein content of seaweed species from Norwegian waters. A solid method to calculate protein content is through the sum of the proteomic amino acids; however, it can be expensive and beyond the capacities of many laboratories. The most commonly used method to quantify protein is based on the assessment of crude protein from overall nitrogen content, using the traditional nitrogen-to-protein conversion factor of 6.25. However, this approach can be inaccurate when applied to seaweeds, often resulting in an overestimation of their protein content. Specific nitrogen-to-protein conversion factors, calculated from amino acid composition and total nitrogen, give a more reliable protein quantification in seaweeds. However, no such factors are available for species from Norwegian waters. This study was designed to characterize the amino acid composition of 21 seaweed species from Norwegian waters and use the amino acid data to estimate protein contents of the seaweeds. Crude protein analysis (nitrogen × 6.25) was performed and resulted in overestimation (18–44 %) of the protein content compared to the sum of proteomic amino acids. Specific nitrogen-to-protein conversion factors, calculated for each species, ranged from 3.53 ± 0.1 to 5.13 ± 0.1. This study provides nutritional data on Norwegian seaweeds, covering a relatively wide range of species. Moreover, it is the first study to assess nitrogen-to-protein conversion factors on such species.